Reproductive/Safe Motherhood Knowledge of Nurses in a Tertiary Care Hospital, Lahore - Umbreen Fatima, Syed Ali Haider Bukhari, Humaira Zareen, Illyas Anjum, Syed Azhar Abbas Naqvi, Syed Aftabalam Gillani, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: According to WHO the reproductive health is defined as “a state of complete physical, mental, social well-being, and not merely the absence of disease or infirmity, reproductive health addresses the reproductive processes, functions and systems at all stages of life. It is estimated that 585,000 women die each year worldwide due to the complications from pregnancy, child birth, abortions and other conditions. The incidence of morbidity, mortality due to unwanted pregnancy and Sexually Transmitted Diseases (STD) are increasing day by day in the whole world. Objectives: To explore the knowledge of nurses regarding reproductive health and safe motherhood and to identify gaps in their knowledge. Place and Period of Study: Lahore General Hospital Lahore from 11th July 2013 to 10th August 2013. Study Design: Cross-sectional descriptive study. Methodology: One hundred and eighty eight nurses were approached; time and date were decided according to their comfort. Interview was conducted after taking informed verbal consent from every nurse confidentiality and privacy was maintained. Results: There were 64 (34%) between 21-25 years, 90 (47.9%) between 26-30 years, 29 (15.5%) between 31-35 years and 5 (2.6%) between 36-40 years. One hundred and sixty four (87.2%) nurses having basic education of BSc Nursing and 24 (12.8%) had done additional diplomas. 74 (39.3%) were having the knowledge of less than 3 or 3 steps of newborn care, while 53 (28.3%) were having the knowledge of greater than 3 steps of newborn care and 61 (32.4%) told all the steps of newborn care. There were only 49 (26.1%) who knew when bath to be given to a newborn, while 99 (52.7%) told that bath to be given within 8-12 hours and 40 (21.3%) narrated that bath to be given immediately. There were 135 (82.3%) nurses who did B.Sc nursing and they were not having the knowledge of RH definition while 13 (54.2%) nurses who did BSc Nursing with additional diplomas were not able to tell about the RH definition. There were 29 (17.7%) nurses with BSc, who had the knowledge of RH definition while 11 (45.8%) nurses who did B.Sc nursing with diplomas, had knowledge of RH definition. This shows a strong association that nurses with additional diplomas had better knowledge than those who did only BSc nursing. Conclusion: Overall the nurses were deficient in their knowledge and they were very vague about the knowledge and they did no refresher training courses. Keywords: Nurses knowledge, Reproductive health, Safe motherhood, Breast feeding, Newborn care